Dipole Antenna Designs For UHF RFID Passive Tag - Keskin, Nesem; Imeci, Taha; Rahman, Shah M. T.; Karacuha, Ertugrul (IEEE, 2014)
Use of REID systems have become popular in many areas such as service, purchase and distribution logistics, manufacturing and material flow to provide information about people, animals and products. Hence, to improve the efficiency of these systems, the amount of research work in this field is increasing. In addition to these works, a considerable amount of research has also been conducted to spread the signal to wideband in order to improve the data transfer consuming less power instead of sending the signal in narrow band with more power. Furthermore, energy consumption can be reduced by using wideband technology. In this study, the goal is to design an antenna that operates in the range 800-1400MHz UHF RFID frequencies with wideband. To design the dipole antenna that can be operated across wide frequency bands, a patch antenna is used. These passive dipole antennas are designed for REID tags. The EPC Gen2 (EPCglobal UHF Class 1 Generation 2) standard is supported in ISO/IEC 18000 for REID.
Keywords: Engineering; Telecommunications